Real-world pharmacovigilance reports of hepatitis A inactivated and hepatitis B (recombinant) vaccine: insights from disproportionality analysis of the vaccine adverse event reporting system - Zhou, Yuhang; Wang, Yue; Feng, Yun; Zhang, Huiyue; Sun, Tao; Xu, Junnan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHepatitis A Inactivated and Hepatitis B (Recombinant) Vaccine (Hep AB) was approved for use in 2001. Hep AB demonstrates satisfactory efficacy in protecting the public from hepatitis virus infections. However, there is a lack of recent real-world report on its adverse events (AEs).MethodsWe retrieved US AE reports related to Hep AB vaccination from VAERS for the period 2020-2024. We used four algorithms: Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN) and Multi-Item Gamma-Poisson Shrinkage (MGPS) to examine AE signals. The ROR and PRR algorithms have higher sensitivity but lower specificity. However, BCPNN and MGPS compensate for this limitation. Combining all four algorithms helps reduce false-positive signals. In addition to the general population, we also focused on reports stratified by gender.ResultsWe retrieved 1,640 eligible reports from VAERS. In the general population, we identified two AE signals at the System Organ Classification (SOC) level. Additionally, we found 39 AE signals at the Preferred Term (PT) level. Among these, endocrine disorders were identified for the first time as AE signals. In the subsequent gender stratified analysis, more AE signals were identified in females compared to males. Notably, signals for endocrine disorders (autoimmune thyroiditis and Graves’ disease) were detected in females, whereas no such signals were found in males.ConclusionsWe conducted a comprehensive examination of the recent AE reports for Hep AB and identified unexpected AEs, particularly in females. These findings will provide valuable insights into future evidence-based surveillance strategies of Hep AB.